Real-time data coupling for hybrid testing in a geotechnical centrifuge - Idinyang, Solomon; Franza, Andrea; Heron, Charles M.; Marshall, Alec M. (Thomas Telford, 2018)
Geotechnical centrifuge models necessarily involve simplifications compared to the full-scale scenario under investigation. In particular, structural systems (e.g. buildings or foundations) generally can’t be replicated such that complex full-scale characteristics are obtained. Hybrid testing offers the ability to combine capabilities from physical and numerical modelling to overcome some of the experimental limitations. In this paper, the development of a coupled centrifuge-numerical model (CCNM) pseudo-dynamic hybrid test for the study of tunnel-building interaction is presented. The methodology takes advantage of the relative merits of centrifuge tests (modelling soil behaviour and soil-pile interactions) and numerical simulations (modelling building deformations and load redistribution), with pile load and displacement data being passed in real-time between the two model domains. To appropriately model the full-scale scenario, a challenging force-controlled system was developed (the first of its kind for hybrid testing in a geotechnical centrifuge). The CCNM application can accommodate simple structural frame analyses as well as more rigorous simulations conducted using the finite element analysis software ABAQUS, thereby extending the scope of application to non-linear structural behaviour. A novel data exchange method between ABAQUS and LabVIEW is presented which provides a significant enhancement compared to similar hybrid test developments. Data are provided from preliminary tests which highlight the capabilities of the system to accurately model the global tunnel-building interaction problem.